Innovation level of onion commodity management in Galung Lombok Village, West Sulawesi, Indonesia - Akhsan, Akhsan; Nurlaela, Nurlaela; Astina, Astina (Anjoro: International Journal of Agriculture and Business, 2023)
Beetroot is a food source that is rich in nutrient value, including carbohydrates, minerals, vitamin C and betalains as a source of, to secure the supply of shallots (bamer) is to encourage the use of True Seed Shallots (TSS) seeds for higher productivity. This research was conducted in Galung Village, Lombok, Tinambung District, Polewali Mandar Regency, using 38 respondents or farmers selected by simple random sampling, considering that the characteristics of shallot farming are homogeneous. Data processing was done using Descriptive Quantitative Analysis using the IBM Statistics SPSS Version 25 application to obtain correlation test results and Scatter Plots. This study aims (1) to determine the distribution of innovation adoption rates and (2) to determine the relationship between innovation adoption rates on the dependent and independent variables of the shallot commodity. The results of this study show the results of the distribution of innovation adoption rates, namely there are 16 farmers with high and low categories, respectively, and as many as six farmers in the medium category, and the results on the Spearman's rank correlation test obtained a value of 0.319, and it is stated that there is a relationship between the level variables of adoption of innovation and productivity. The Scatter Plot graph shows that in quadrant III, it is noted that the value of the level of innovation adoption and productivity has a tendency together to obtain a high value of the distribution.